The organized teacher's guide to being a creative teacher - Springer, Steve; Alexander, Brandy; Persiani-Becker, Kimberly (New York McGraw-Hill, 2019)
To keep your students engaged in the classroom, you have to get them excited about learning. This award-winning resource offers hundreds of creative ideas to reenergize your lesson plans for any subject, across all grades (K-6) from waking up the tired book report to making math fun. This new edition has been revised to align with the Common Core Standards and boosts content that is accessible online with many pages of reproducible content including worksheets, project ideas, templates for journal pages, and more. From submarine sandwich book reports to graphic organizers to help incorporating writing into math curriculum, this book has ideas and materials to add zing to your classroom plans as you incorporate the Common Core Standards.
Book reports -- Math -- Writing -- Science -- Social sciences -- Art.
"Perfect for Teachers of Grades K-6" -- Cover page 1.
"An encyclopedia of ideas to engerize your curriculum. Curriculum, projects, and activities for each grade level. Be prepared for any grade, any class, any subject. Newly revised with fresh content. New online materials for your classroom!"--Cover page 1.
Downloadable, editable pdf templates may be obtained from the McGraw-Hill Education Media Center at http://mhprofessional.com/mediacenter.
Includes bibliographical references (pages 323-326).
Grades K-6.
System requirements: PC or MAC computers with Adobe Reader.
Keywords: Creative teaching -- United States -- Handbooks, manuals, etc; Activity programs in education -- United States -- Handbooks, manuals, etc; Creative activities and seat work -- Handbooks, manuals, etc